IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK DALAM PENYAJIAN LAPORAN KEUANGAN PADA PT AURINDO JAYA PERKASA - Shinta Lia Lestari; Diana Gustinya (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
The reason for this research is that the researcher wants to complete the financial report of PT Aurindo Jaya Perkasa based on SAK ETAP and the finance department of PT Aurindo Jaya Perkasa also want to know how to compile and present the complete SAK ETAP in its financial statements. The purpose of this study was to find out how to compile and present a complete financial statement based on SAK ETAP on PT Aurindo Jaya Perkasa. This research method uses qualitative descriptive analysis method, which analyzes the problem by describing the financial statements of PT Aurindo Jaya Perkasa which includes measurement, presentation and disclosure based on SAK ETAP. The results of this study indicate that PT Aurindo Jaya Perkasa has not compiled and presented a complete financial report in accordance with SAK ETAP. The conclusion of this study is that PT Aurindo Jaya Perkasa has not completed its financial statements in accordance with SAK ETAP because in the financial statements of PT Aurindo Jaya Perkasa there is only an income statement and a statement of financial position.